Chlordiazepoxide-induced delirium in a patient undergoing alcohol withdrawal: a case report - Melissa A. Arabadjief; Omar H. Elsayed; Sabina Bashir; Meenakshi R. Gundumalla; Derek S. Menefee; Cody L. Bergman; Nayeem Z. Moulana; Rif S. El-Mallakh (Journal of Medical Case Reports, 2022)
Abstract Background Ethanol dependence is associated with a discontinuation withdrawal delirium. Chlordiazepoxide is frequently successfully used in its treatment. Case presentation A 27-year-old, Caucasian female with ethanol dependence who had objective symptoms of withdrawal experienced worsening of her delirium after administration of chlordiazepoxide, but improved with lorazepam and cleared with discontinuation of benzodiazepine administration. Conclusions Worsening of delirium appears to be related to the specific use of chlordiazepoxide, but the mechanism of this effect is not clear. While this case does not alter the standard care of ethanol dependence, it does alert clinicians that our treatment approach may not be fully benign.